Canada's Energy Future in an Age of Climate Change. How Partisanship, Polarization and Parochialism are eroding Public Confidence - Cleland, Michael; Gattinger, Monica (Université d'Ottawa | University of Ottawa, 2019)
This paper aims to unpack the core challenges and opportunities when it comes to building confidence in public authorities making decisions about Canada’s energy future in an age of climate change. It provides an analysis of how Canada’s political and economic context relative to other countries is fundamental to the course of its energy future, and why it is vital that energy and climate decision making be undertaken with that full context in mind. Importantly, the paper underscores that public confidence in those making decisions about Canada’s energy future in an age of climate change – the focus of Positive Energy’s next three years of research and engagement – will be shaped fundamentally by many factors specific to energy (e.g., the role of local and Indigenous governments, the future for oil and gas, social acceptance of energy technologies, and relationships between policymakers, regulators and the courts), but it will also be shaped by a number of political, economic and social trends well beyond energy, climate or environmental issues.
Keywords: Polarization; Canada; Energy policy; energy regulation; oil and gas; renewable energy; public confidence; climate change; Positive Energy; Indigenous Rights